GRAMMATICALIZATION VIA SEMANTIC BLEACHING IN IDIOMATIC CONSTRUCTIONS: A SCIENTOMETRIC APPROACH - Nugraha, Danang Satria (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This scientometric study investigated the evolving intellectual landscape concerning the interplay between grammaticalization and semantic bleaching within idiomatic constructions. To achieve this objective, the study meticulously analyzed a dataset comprising 356 scholarly publications extracted from the Scopus database, spanning the period from 2014 to 2024. The research employed bibliographic data analysis and keyword clustering as primary analytical techniques. Our findings reveal four salient thematic clusters: “theory” (31.62% of notable keywords), “grammaticalization” (30.88%), “corpus & frequency” (29.41%), and “syntax & change” (8.09%). These clusters comprehensively underscore the most notable theoretical frameworks, methodological approaches, and specific linguistic subfields that significantly contribute to this active research area. To some extent, the findings provide a detailed overview of current research and suggest avenues for further investigations, particularly those employing corpus-based methods and incorporating insights from cognitive linguistics and construction grammar to further explore grammaticalization in specific languages, such as Indonesian.This scientometric studyinvestigated the evolving intellectual landscape concerning the interplay between grammaticalization and semantic bleaching within idiomatic constructions. This study employed a scientometric approach to map the intellectual landscape of this research domainTo achieve this objective, , the study meticulously analyzed a dataset comprising analyzing 356 scholarly publications extracted from the Scopus database, spanning the period from (2014 – to 2024). Through bibliographic data analysis and keyword clustering, we identified key trends, influential authors, and thematic clusters.The research employed bibliographic data analysis and keyword clustering as primary analytical techniques. As a part or the findings,Our findings reveal four prominent salient thematic clusters: emerge, highlighting research foci on “theory” (31.62% of notable keywords), “grammaticalization” (30.88%), “corpus & frequency” (29.41%), and “syntax & change” (8.09%). These clusters reveal comprehensively underscorethe most notable theoretical frameworks, methodological approaches, and specific linguistic subfields contributing to this research area.that significantly contribute to this active research area. To some extent, the findings provide a detailed overview of current research and suggest avenues for further investigations, particularly those employing corpus-based methods and incorporating insights from cognitive linguistics and construction grammar to further explore grammaticalization in specific languages, such as Indonesian.